Hindsight 2020: Reflections of community visions from the past. Issue 1 (2nd January 2021) - Gibson, Huston; Clanahan, Christopher M.
ABSTRACT: This study retrospectively analyzes a dozen "Vision 2020" community plans, with critical analysis of their vision statements and subsequent implementation. Evaluation and appraisal review of plan implementation is a valuable component of the community development process, as reflection fosters improvement. This study uses document data and personal interviews with local community professionals across the United States to discover outcomes and assess what planners identify as the barriers and gateways to success when implementing community visions. A varied sample was extracted from long-range plans leading up to year 2020 which exemplified a focus on community visioning. Findings discuss what worked, what did not work, and lessons learned. Subsequent discourse is intended to aid community development professionals with future community visioning processes and implementation.